Hak Pencipta Atas Performing Right dalam Peraturan Hak Cipta Indonesia dan Konvensi Internasional - Regyna Putri Willis; Zulfikar Jayakusuma; Aditya Wahyu Tiaraputri (Jurnal Hukum Lex Generalis, 2022)
The creation of musical creation has the right to perform his creation in public including in any way and process the communication of his performance. For example, the copyright of a song may give birth to the related rights in the form of Performer's Rights if the creator gives permission to the artist to perform (to perform) the song in question, both in a Live Show and in the form of recording work. The type of research used is normative juridical. Until 2021, Performing Rights is still a thorny issue in the Indonesian music industry so one of the steps taken by the government is to issue Government Regulation No. 56 of 2021 on The Management of Song and/or Music Copyright Royalties. In addition, there are also international arrangements in several conventions and treaties.